EXPERIMENTAL STUDIES ON THE HYDROTHERMAL PROCESS OF MUNICIPAL SOLID WASTE TO PRODUCE SOLID FUEL - ERRY BRAMANTYO (NIM : 13105050); Pembimbing : Dr. Ir. Ari Darmawan Pasek, GEOVANI
In Indonesia, the electricity demand increases every year due to the increase in the economic growth. Most of the electricity generate from a fossil fuels, which is coal is one of them. However the availability of the coal is limited, so the other alternative fuel is needed. On the other hand, the production of Municipal Solid Waste (MSW) in many cities is increasing and hard to manage. In order to solve those problems, the MSW and coal are used together as a fuel, so the using of the coal will be decreased. Because of the MSW’s calorific value is not high and the moisture level is too high as a fuel, it has to be managed. One of the management of MSW is by using a hydrothermal process. The hydrothermal process was done using a laboratorium scale apparatus by using the Bandung’s MSW which is operated at temperature 215 oC and pressure 20 bar. The result of the experiments show that the process period and the water amount which are used in hydrothermal process, affect to the proximate composition. The affection are the MSW’s moisture content and the volatile matter are decrease and the fixed carbon is increase, so the MSW’s calorific value will be increased. Based on the ultimate experimentation, it is showed that the use of hydrothermal process produces MSW fuel with a mass fraction 65.37% of carbon total, 5.63% of hydrogen total, 2.75% of nitrogen, 0.1499 % of sulfur toatal, 2.70% of ash and lastly, 23.9% of oxygen.